Evaluation of a group acceptance commitment therapy intervention for people with knee or hip osteoarthritis: a pilot randomized controlled trial - Clarke, Simon P.; Poulis, Nektaria; Moreton, Bryan J.; Walsh, David A.; Lincoln, Nadina B. (Taylor and Francis online, 2016)
OBJECTIVES: The aim was to evaluate an Acceptance commitment therapy (ACT) intervention for people with knee or hip osteoarthritis; a related aim was to compare treatment effects from Rasch-transformed and standard scales. METHODS: Participants were recruited from a research database and outpatient rheumatology and orthopaedic clinics at two hospitals. Eligible participants were randomly allocated to either intervention or usual care. Intervention comprised six-sessions of group ACT. Outcomes were assessed two and four months after randomization. Rasch-transformed and standard self-report measures were compared. Qualitative interviews also explored the acceptability of the intervention. RESULTS: Of 87 people assessed for eligibility, 31 (36%) were randomized. The main reason for non-randomization was that participants received surgery. Of the 16 participants randomized to intervention, 64% completed ≥50% of the scheduled group sessions. Follow-up data was complete for 84% participants at two months and 68% at four months. Outcome analysis demonstrated important differences between the Rasch-transformed and standard scales. There were significant differences between the groups in pain. Qualitative interviews with seven participants suggested the intervention was acceptable. CONCLUSIONS: ACT for osteoarthritis is likely to be an acceptable treatment option for people with osteoarthritis. Progress to a definitive trial is warranted. Rasch-transformed outcome scales are preferable in clinical trials where possible. Implications for Rehabilitation Acceptance commitment therapy (ACT) is an effective treatment for many pain conditions andcould be a useful intervention for people with osteoarthritis who have high levels of pain. Rasch analysis is a measurement technique that may enable greater precision in detectingmeaningful treatment effects in routine clinical outcomes. The ACT intervention was successful in reducing pain and sleep difficulties and there werenotable differences in effects between standard and Rasch-transformed scales. In a relatively small trial, ACT may to be an acceptable intervention for people with osteoarthritisand progress to a definitive trial is warranted.